Blood Lead Levels in Rag-Pickers of Kathmandu and its Association with Hematological and Biochemical Parameters - Gautam, Keyoor; Pant, Vivek; Pradhan, Santosh; Pyakurel, Devish; Bhandari, Bijay; Shrestha, Abha (EJIFCC, 2020)
Lead poisoning is a common health problem in Nepal and there are a limited number of studies on blood lead levels in various population groups. Rag-pickers are those people who visit from house to house to collect the materials that can be recycled and thus earn their livelihood. The present study was designed to evaluate blood lead level (BLL) and its relationship between hematological and biochemical parameters in rag-pickers working in Kathmandu. An observational cross-sectional study among 50 ragpickers working in the selected area of Kathmandu was done in May 2019 after obtaining ethical approval from the Nepal health research council. Capillary and venous blood was drawn from each participant after written consent to measure the BLL, aspartate aminotransferase, alanine aminotransferase, total bilirubin, creatinine, glucose and to test for a complete blood count. Whole blood was also screened for the presence of hemoglobin variants in cases with abnormal red blood cell indices. Data was analyzed using SPSS (Version 20.0). All rag pickers were men with mean age of 32.56 ± 12.51 years. The mean BLL among ragpickers was 11.6 ± 7.23 μg/dL. High eosinophil count was found (8.27 ± 5.49 %) in 27 cases (54%) having no significant association with BLL. The mean BLL was higher (12.89 μg/dL) in a cohort of workers who pick and recycle electronic waste. Beta-Thalassemia trait was seen in four cases, all of them had high BLL. No significant association of BLL with the number of years worked by rag picker was found. Similarly, no significant association of BLL with hematological and biochemical parameters was found. Rag-pickers working in Kathmandu are at increased risk of lead toxicity. The use of protective gloves, masks, shoes and clothes along with a regular medical examination of this vulnerable group is recommended.